Feasibility of waste mother liguor of monosodium glutamate used as nutrition solution for soilless cultivation - ZHOU Xue-lai; ZHOU Chai-mei; ZHU Ri-qing; FANG Ping (浙江大学学报. 农业与生命科学版)
The effects of waste mother liquor of monosodium glutamate and complete nutrition solution as nutrient supplement on tomato plants were compared. The tomato plants were grown on 4 different culture matrixes all prepared mainly from waste culture medium for edible fungi. Results of our experiment showed that on matrixes ②, ③ and ④, where soil was an indispensable component, the growth and development of tomato plants were basically normal, whereas growth of plants on matrix ①, in which the soil component was lacking, was relatively poor due to occurrence of secondary fermentation.